A very private murder - Pawson, Stuart, 1949- (D.I. Charlie Priest series ;, 2011)
D.I. Charlie Priest is on gardening leave - the neighbors have complained about his weeds - when the call comes. Ghislaine Curzon, girlfriend of one of the royal princes, is in Heckley to open the Curzon Centre, a new shopping mall and conference facility. But as she reveals the commemorative plaque at the opening ceremony it looks like someone has got to it first, defacing it with a single obscene word in foot-high red letters. The visiting dignitaries are aghast and the chief constable insists on Charlie investigating the case. Charlie would rather be investigating the burglaries perpetrated by a two-man gang, armed with a pit bull terrier, but he welcomes the opportunity to meet Ghislaine, known as Grizzly to her friends, at the family's stately home in East Yorkshire. He also meets and befriends Toby, her precocious thirteen-year-old sister. The jollities cease, however, when the mayor of Heckley and driving force behind the construction of the Curzon Centre is found dead, killed by a single shot to the head. The subsequent investigation involves a cornucopia of characters from the rich farmland of East Yorkshire. As one of them tells Charlie: 'We do things different in the country'. Charlie is not averse to doing things differently himself, to the displeasure of the superintendent in charge of the investigation, and it's going to take more than standard police procedure to crack this case